Knowledge and practices among healthcare workers regarding dengue in Togo - Wendpouiré I.C. Zida-Compaore; Fifonsi A. Gbeasor-Komlanvi; Martin K. Tchankoni; Arnold J. Sadio; Yao R. Konu; Amegnona Agbonon; Didier K. Ekouevi (AOSIS, 2022)
In Togo where malaria is endemic, because main signs of malaria and dengue are similar, the use of malarial drugs first could contribute to a delay in the diagnosis of dengue and the dissemination of the disease. Thus, it is important that healthcare workers (HCW) have a good knowledge of these diseases. To assess the knowledge, and practices regarding dengue infection among HCW in Togo. A cross-sectional study was carried out from November 2020 to March 2021 among HCW in Togo. A pre-tested digital questionnaire was used for data collection. Based on clinical signs of dengue, preventive measures, infection type and disease type, a knowledge score was constructed with eight questions. A total of 334 HCW with median age 32 years, IQR:(28-38) responded to the survey and the sex ratio male/female was 5.9. The majority (94.0%) of HCW have heard about dengue through training (73.3%), internet (38.0%) and media (33.2%). Compared with lower executive HCW, senior manager were more knowledgeable about the causative agent, the symptoms and preventive methods of dengue infection (p0.001). Globally, good knowledge (score ≥6) about dengue was found for 47.1% of HCW. More than 9 out of 10 HCW (91.3%) reported the lack of dengue diagnostic tools. Providing health structures with dengue diagnostic tools and training health personnel in their use in any febrile patient with a negative or positive malaria test would help prevent dengue epidemic.